Penerapan model discovery learning untuk meningkatkan kemampuan berpikir kritis siswa pada materi aritmatika sosial - Septiani, Mariah; Rohaeti, Euis Eti; Bernard, Martin (IKIP Siliwangi, 2023)
This research is motivated by the importance of knowing the mathematics learning model to improve students' critical thinking skills on social arithmetic material. This study aims to describe the effectiveness of the discovery learning model to improve students' critical thinking skills on social artifacts. This study uses a quantitative approach using a quasi-experimental method. The population of this research is class VII SMPN 6 Cimahi. The sampling technique used sampling technique. Class VII A and VII B research samples. The research instruments used were test questions and observation sheets. The data analysis technique used is prerequisite analysis and hypothesis testing. The results of the research show that the discovery learning model is effective for increasing students' critical thinking skills in social arithmetic material. This is shown through the results of the t-test using the independent sample t-test obtained a significant value at (2-tailed) = 0.012. The results of the t test show that the application of the discovery learning model applied in class VII A causes an increase in students' critical thinking skills.